2016
DOI: 10.3389/fpubh.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Predict Major Depressive Disorder after 15 Years among Whites but Not Blacks

Abstract: BackgroundBlack–White differences are shown in psychosocial and medical correlates of depressive symptoms and major depressive disorder (MDD). The current longitudinal study compared Blacks and Whites for the association between baseline depressive symptoms and subsequent risk of MDD after 15 years.MethodsData were obtained from the Americans’ Changing Lives (ACL) Study that included 3,361 individuals (2,205 Whites and 1,156 Blacks) from 1986 to 2001. Baseline depressive symptoms measured using an 11-item Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 58 publications
(97 reference statements)
8
59
0
Order By: Relevance
“…Comparing sociodemographically matched Black and White pregnant women, Canady et al found that the positive item “ happy ” was the only item among the 20 items with different loadings between Blacks and Whites (29). This finding was similar to what Moazen-Zadeh and Assari found recently investigating the 11-item version of the CES-D scale (24). …”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Comparing sociodemographically matched Black and White pregnant women, Canady et al found that the positive item “ happy ” was the only item among the 20 items with different loadings between Blacks and Whites (29). This finding was similar to what Moazen-Zadeh and Assari found recently investigating the 11-item version of the CES-D scale (24). …”
Section: Introductionsupporting
confidence: 92%
“…In this study, the CES-D scale item “ people disliked me ” loaded better into the positive affect factor in Blacks but better into the interpersonal problems factor in Whites (24). In another cross-sectional study on NSAL data using the 12-item CES-D scale, CES-D scale negative affect and interpersonal problem domains were more strongly associated with CIDI-based major depressive disorder (MDD) in Blacks compared to Whites (25).…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations